2010
DOI: 10.1038/cgt.2010.2
|View full text |Cite
|
Sign up to set email alerts
|

Gene-modified tumor vaccine secreting a designer cytokine Hyper-Interleukin-6 is an effective therapy in mice bearing orthotopic renal cell cancer

Abstract: Although Renal Cell Cancer (RCC) is known to be immunogenic, clinical efficacy of various immunotherapeutic approaches remains unsatisfactory. Novel targeted therapies showing cytostatic rather than cytotoxic activity are unable to cure RCC patients. In our studies, we evaluated the therapeutic efficacy of whole-cell vaccine based on irradiated murine RENCA cells genetically modified to secrete designer cytokine-Hyper-IL6 (H6)-comprising IL-6 and soluble IL-6 receptor. An orthotopic RCC model based on a subcap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…One explanation might be the inability of activated T cells to overcome tumor-derived immune suppression. Several reports have shown that the accumulation of tumor-induced suppressor cells, including myeloid-derived suppressor cells and regulatory T cells, is an impediment to the induction of protective antitumor immunity in RCC patients [47], [48], [49], [50] and in murine Renca models [31], [51], [52], [53]. We applied Ad5mTRAIL+CpG therapy to mice in which the primary renal tumors were left intact.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation might be the inability of activated T cells to overcome tumor-derived immune suppression. Several reports have shown that the accumulation of tumor-induced suppressor cells, including myeloid-derived suppressor cells and regulatory T cells, is an impediment to the induction of protective antitumor immunity in RCC patients [47], [48], [49], [50] and in murine Renca models [31], [51], [52], [53]. We applied Ad5mTRAIL+CpG therapy to mice in which the primary renal tumors were left intact.…”
Section: Discussionmentioning
confidence: 99%
“…Renal tumors produce additional factors that may favor their infiltration by NK cells, consistent with NK cells having a role in RCC. Strong secretion of IL6 by RCC cells may favor tumor growth (Alberti et al, 2004), but induce an inflammatory environment and recruit NK cells (Wysocki et al, 2010). The chemoattractant cytokine, IL8, in the environment of renal tumors may also favor the recruitment of NK cells (Segerer et al, 2006) and induce their activation together with the membrane IL15 present on renal cells (Wittnebel et al, 2007).…”
Section: Mutated Vhl Rcc Cells and Nk Cell Activationmentioning
confidence: 99%
“…Whole cell-based vaccines can be autologous or allogeneic, and may be modified (e.g., to express immunomodulatory molecules), 30 - 33 fused with DCs, 34 - 36 or unmodified (e.g., in the form of lysates or irradiated whole cells) 37 , 38 . The promise of this vaccine formulation has been primarily attributed to the multi-epitope nature of the immunogen.…”
Section: Discussionmentioning
confidence: 99%